Epigenetics, Bone Remodeling and Osteoporosis - Yang, Shaoqing; Duan, Xiaohong (Current Stem Cell Research & Therapy, 2018)
Background: Osteoporosis is a common degenerative bone disease which is characterized with decreased bone strength and increased risk of fracture. The abnormal bone metabolism homeostasis, especially in osteoclastic function, takes a fundamental role in osteoporosis pathogenesis. In the past decade, epigenetic regulation of bone homeostasis are widely investigated and considered as a vital factor in the regulation of the differentiation and functions of osteoblasts, osteoclasts and osteocytes. The relationship between osteoporosis and epigenetic regulations has gradually become as an important issue in the mechanism study of osteoporosis. Objective: In this review, we summarize the recent progresses of epigenetic regulation mechanism in bone development and remodeling, and emphasize the epigenetic features of osteoporosis and the potent therapy application of epigenetic drugs for osteoporosis. Conclusion: DNA methylation and histone modification regulated bone development and remodeling via affecting both osteoblastogenesis and osteoclastogenesis. And the abnormal epigenetic status is relevant to bone disease such as osteoporosis and osteoarthritis. Several inhibitors of DNMTs or HDACs exhibit a potential application for osteoporosis, and the side effects of these drugs should also be considered in the future applications.
Keywords: bone remodeling